DESIGNING CULTURALLY CONSCIOUS ALTERNATIVE DISPUTE RESOLUTION TO FOSTER ASIAN ECONOMIC DEVELOPMENT - Mrs. Herliana (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2011)
Creating an Asian model of alternative dispute resolution which considers Asian cultures is important. A mere adoption of western standard will less likely accommodate Asian’s unique way of handling disputes. Culture-related problems can be avoided if international commercial mediation or arbitration is tuned in to cultural needs and expectations. Penyusunan model alternatif penyelesaian sengketa gaya Asia yang mengakomodasi budaya setempat penting untuk dilakukan. Penerapan standar barat tidak selamanya cocok dengan cara unik orang Asia dalam memandang suatu sengketa. Konflik kultural dapat dihindari apabila mediasi atau arbitrase bisnis internasional disesuaikan dengan kebutuhan budaya setempat.